Microstructure Evolution of 5052 Aluminum Sheet in Electromagnetic High-Speed Impact - Fei Feng; Jianjun Li; Yunjun Zhang; Liang Huang; Hongliang Su; Shijing Cao; Guangbao Shao; Rongchuang Chen (Metals, 2020)
Electromagnetic forming (EMF) is a high-speed forming technology, which can not only improve the formability of hard-to-form materials but also reduce springback. Electromagnetic high-speed impact can further improve the formability compared with electromagnetic free forming. The microscopic deformation mechanism of electromagnetic high-speed impact of aluminum alloy is discussed in this paper. The microstructures of electromagnetic high-speed impact of an aluminum alloy sheet were characterized. The microscopic deformation mechanisms of electromagnetic forming and electromagnetic high-speed impact were shown, respectively. The research results showed that electromagnetic high-speed impact could significantly improve the microhardness of the workpiece. The grains broke up and then became small subgrains during electromagnetic high-speed impact. The deformation mechanism was dominated by dislocation cross slip under electromagnetic high-speed impact.